Effects of Wind on Virtual Plants in Animation - Tina L. M. Derzaph; Howard J. Hamilton (International Journal of Computer Games Technology)
This paper presents the Growth-Flow method for animating the effect of wind on the motion and growth of virtual plant branches and leaves. The method incorporates changes to the growth rate when a plant is exposed to winds with speeds higher than a threshold. In particular, growth rate is reduced in branch elongation, increased in the branch radius, reduced in leaf length, and increased in leaf thickness. In addition, when a plant is exposed to wind for long time periods, the branch growth angle is changed to align more closely with the wind vector. The Growth-Flow method incorporates all these effects on growth and motion due to wind in one algorithm.